O humor nas charges de Angeli: um estudo da construção linguístico-discursiva e dos efeitos de sentido no discurso humorístico - Pereira, Cibeli Morais (2018)
This present piece of work has as a objective to analyse the linguistic discursive construction found in the cartoons by Angeli. The corpus is composed by four cartoons published by Folha de São Paulo newspaper relating the period from January 2016 to September 2016, regarding Dilma Rousseff´s impeachment. We believe that cartoons provide rewarding experiences with issues related to language and humour as a social phenomenon which expresses an opinion leader character. The theoretical principles are based on humour concepts presented and discussed in the studies of Bergson (1993), Propp (1992), Travaglia(1990), as well as in the Discourse Analyses in media context from Charaudeau`s perspective (2005, 2006, 2009, 2014, 2015). Firstly, we proceed to present the corpus and historical aspects which involve the selected cartoons. We resumed the history, trying to understand how humour was explained by scholars and theoreticians chosen for this study. We managed to identify the linguistic elements of humour in cartoons and the effects of understanding of such cartoons. Finally, after corpus analyses, we realized that humour not only criticizes, but also derides those who distance from social standards